2022
DOI: 10.1021/acs.jafc.2c05940
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Discovery of Sorbicillinoid Pigments with Anti-Inflammatory Activity from the Sponge-Derived Fungus Stagonospora sp. SYSU-MS7888 Using the PMG Strategy

Abstract: An effective identification and discovery of fungal pigments is very important to illustrate the role of fungal pigments in the life process and conduce to the discovery of new bioactive and edible pigments. The phenotype combined with metabolomic and genomic (PMG) strategy led to the discovery and characterization of three new sorbicillinoid pigments, stasorbicillinoids A–C (1–3), and five known analogues (4–8) from the sponge-derived fungus Stagonospora sp. SYSU-MS7888. Their structures were elucidated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“….59,21.81, 19.79, 18.89. The NMR data of compound 5 were consistent with the literature data 9. Compound 6: UV λmax (MeOH) 197, 298, 383 nm; HR-ESIMS m/z: 495.2027 [M − H] − (calcd for C 28 H 31 O 8 , 495.2024); 1 H NMR (600 MHz, DMSO-d 6 ): δ 7.23 (dd, J…”
supporting
confidence: 85%
See 3 more Smart Citations
“….59,21.81, 19.79, 18.89. The NMR data of compound 5 were consistent with the literature data 9. Compound 6: UV λmax (MeOH) 197, 298, 383 nm; HR-ESIMS m/z: 495.2027 [M − H] − (calcd for C 28 H 31 O 8 , 495.2024); 1 H NMR (600 MHz, DMSO-d 6 ): δ 7.23 (dd, J…”
supporting
confidence: 85%
“…SYSU-MS7888 was sequenced by secondgeneration sequencing, and antiSMASH analysis of the sequenced genome suggested that cluster 320.1 encodes a BGC (sta cluster) that shares significant similarity with the sorbicillinoid BGCs from T. reesei QM6a and P. chrysogenum. 9,20,21 (Figure 2). Cluster 320.1 harbors a pair of PKSs, a hr-PKS (StaC) and a nr-PKS (StaB), which are presumably responsible for the formation of sorbicillin monomer (1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marine fungi are known to produce a wide range of active substances with biomedical and agricultural values. , As part of our ongoing search for bioactive molecules from marine fungi, we obtained the fungus Beauveria felina SYSU-MS7908, which showed an antagonistic effect on G. citri-aurantii.…”
Section: Introductionmentioning
confidence: 99%